Tuning molecular emission of organic emitters from fluorescence to phosphorescence through push-pull electronic effects - Hai-Tao Feng (Nature Portfolio, 2020)
Though organic emitters with room temperature phosphorescence (RTP) are attractive for various applications, realizing highly efficient and long lifetime emission remains a challenge. Here, the authors report the role of push-pull electronic effects on emission for organic RTP emitters.